INFORMATION AND ANALYTICAL SYSTEM FOR OBTAINING AN INTEGRATED ASSESSMENT OF THE QUALITY OF EDUCATIONAL SERVICES FROM THE POSITION OF CONSUMERS - Azarnova, Tatiana; Barkalov, Sergey; Bondarenko, Yulia; Kalinina, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The aim of the research study is the description of the information analytical system developed by the authors for the formation of an integral linguistic assessment of the quality of educational services from the perspective of three main groups of consumers: employers, students and young professionals. The computation of the integral linguistic quality assessment is based on specially structured information obtained in the course of a voluntary online survey of consumers on specialized quality criteria for groups. A site has been developed for the online survey. The algorithmic support of the information-analytical system is based on the methods SERVQUAL, SWOT-analysis and fuzzy linguistic information processing technologies. The tools of the information analytical system allow us to obtain: linguistic assessments of the quality of services from the perspective of each group of consumers, an integral quality assessment for all consumers and automatically build a SWOT analysis matrix to develop a strategy to improve the quality of the analysed services. In accordance with modern standards of quality management, the approach to quality assessment laid down in the methodology for generating results uses the assumption that the consumer assesses the quality of services based on a comparison of his/her expectations and perceptions of the service during its receipt.